Oat crown rust in Tunisia in 2003 - Allagui, Mohamed Bechir; Chakroun, Mohamed (MTT, 2004)
Crown rust (Cr), caused by Puccinia coronata f. sp. avenae, is generally considered the most widespread and damaging disease of oat in Tunisia. The most important sources of resistance are based on the Pc genes active as racespecific resistance. Sixteen single gene oat lines were sown in 4 sites. Earlyseeded planting were shown to increase early Cr development (Allagui et al. 2002). The conditions of these sites ranged from humid (Sejnane), to subhumid (Lafareg), to semi-arid (Ariana and Bou Rabia). The oat plants were subjected to Cr natural infections during the 2003 to assess with time the most prevalent Cr pathogenic variability. The differential reactions were determined at the maximum Cr attack being in February for Sejnane, in March for Ariana and in April for Lafareg and Bou Rabia. The five lines Pc40, Pc45, Pc46, Pc50 and Pc54 were heavily infested. Infection types ranged between 3 to 4 for these differentials having on the leaf area medium to large uredinia without chlorosis. Reaction of the seven lines Pc48, Pc51, Pc56, Pc58, Pc59, Pc62 and Pc64 varied between site. The four differentials Pc38, Pc39, Pc52 and Pc68 were resistant at Bou Rabia and Ariana. Of these only Pc39 was susceptible in Sejnane but leaf area covered with large uredinia was small (1 %); at Lafareg both Pc52 and Pc68 were susceptible but with only few uredinia on the leaves (1 % and 5 % respectively). According to the nomenclature of Chong et al (2000), reaction of the differentials indicate the Cr virulence phenotypes prevalent in Tunisia ranged from TFRT at Lafareg, to TJFR at Sejnane, to TDFL at Ariana to TBLM at Bou Rabia. The Pc genes, more resistant to oat Cr in Tunisia, were Pc38, Pc39, Pc52 and Pc68. In previous evaluations carried out in 2000-2002, the lines Pc38, Pc39 and Pc68 were equally resistance (Allagui et al. 2002). However, slow rusting with partial resistance is being now more attractive. The most pathogenic variability rendering many genes ineffective was mainly located in Lafareg and Sejnane. These regions are in the neighborhood of the noth-west tunisinan s mountains having different Rhamnus species but not R.cathartica. Surveys on these Rhamnus species, conducted in 2003, showed for the first time in Tunisia that R.lycioïdes is the aecial host for the sexual stage of oat Cr (Hemmami and Allagui. 2003). The high genetic variability of the Cr virulence in these regions could be linked to the aecidial form found on this R.lycioïdes species. Allagui, M.B. et al. 2002. Ann. De l INRAT 75, 205-221; Chong, J. Et al. 2000. Plant Disease 84, 580-585. Hemmami I, Allagui MB, 2003. Proc. of the 10th National Days on Results of Agronomic Research Nabeul (Tunisia).
Keywords: Ka; crown rust; Pc genes; Rhamnus lycioïdes; aecial host; Tunisia